A High Molar Extinction Coefficient Ru(II) Complex Functionalized with cis-Dithiocyanato-bis-(9-anthracenyl-10-(2-methyl-2-butenoic acid)-1, 10-phenanthroline): Potential Sensitizer for Stable Dye-Sensitized Solar Cells. (28th April 2014) - Adeloye, Adewale O.; Ajibade, Peter A.
Abstract : New heteroleptic ruthenium(II) complex was formulated as [Ru(L1 )2 (NCS)2 ], where L1 = 9-anthracenyl-10-(2-methyl-2-butenoic acid)-1, 10-phenanthroline was synthesized and its photophysical properties were studied and compared to previously reported analogue complex containing no anthracene moiety [Ru(L2 )2 (NCS)2 ], L2 = (2-methyl-2-butenoic acid)-1, 10-phenanthroline. The two complexes though exhibit very strong molar extinction coefficient values; however, [Ru(L1 )2 (NCS)2 ] shows better characteristic broad and intense metal-to-ligand charge transfer (MLCT) absorption band and higher molar absorptivity coefficient at (λ m a x = 522 nm, ε = 6.60 × 10 4 M −1 cm −1 ) than that of [Ru(L2 )2 (NCS)2 ] complex, (λ m a x = 446 nm, ε = 4.82 × 10 4 M −1 cm −1 ). At room temperature, long wavelength emissions with strong intensity ratio centered at 660 nm were recorded for [Ru(L1 )2 (NCS)2 ] complex with a bathochromic shift (λ e m = 700 nm) for [Ru(L2 )2 (NCS)2 ] complex. It was shown that the luminescence wavelength characteristic of the complexes may be a function relating to the increasing length of π -conjugation and/or molecular weight. A preliminary cyclic voltammetry of [Ru(L1 )2 (NCS)2 ] complex also exhibits good electroredox activity with oxidation potential of about 1.04 V, significantly better than other Ru(II) polypyridine complexes containing bidentate ligands.